The New Paradigm of Arts Learning - Indrayuda Indrayuda (International Conference on Languages and Arts, 2012)
This article focuses on the new paradigm of arts learning. This study is based on the research in West Sumatera Province, Jambi and Bengkulu area. The findings of this research shown that most students having difficulties in understanding and enjoying the learning process due to conservative methods used by teachers. Teachers must be encouraged and exposed to a new dimensions of teaching and methodologies such as the appreciation re creative and exploration methods and by exploiting the invention of a new media in supporting and delivering the teaching of arts. Keywords: Arts Learning, new paradigm,